„ES GEHT DOCH NICHTS ÜBER EINEN GESUNDEN BREI VON LÜGEN UND PHRASEN“ - Wolfgang Mieder (Proverbium, 2020)
The manipulation and misuse of the German language during the time of National Socialism has been studied in considerable detail. The role that folklore in general and proverbs and proverbial expressions in particular have played has also been investigated. There is also the important diary of the Jewish philologist Victor Klemperer who survived the Holocaust while recording the language of the perpetrators. Adolf Hitler employed a considerable amount of proverbial language in Mein Kampf and his speeches, with Joseph Goebbels making frequent use of proverbs and proverbial expressions in his propagandistic speeches and articles. His voluminous diary that he kept between 1924 and 1945 is replete with proverbs and proverbial expressions. He uses proverbs to justify or to explain the aggressive policies and dangerous actions of the regime. The many proverbial expressions, especially those that refer to various parts of the body (somatisms), express in colloquial language his anti-Semitic tirades and his devious warmongering. Some of these phraseologisms became leitmotifs for his lies and attacks, showing once and for all that proverbial language is by no means sacrosanct and can become a dangerous weapon when used to manipulate, deceive, and violate others. Many contextualized examples show that Joseph Goebbels employed certain words and expressions in such inhumane fashion that they have become taboo today out of respect for the victims of his evil designs.